Interpretation of the 2021 American College of Rheumatology/Vasculitis Foundation guideline for the management of Kawasaki disease - PAN Yan; YAN Xiaohua; KUO Hochang; DING Yan; JIAO Fuyong; JIAO Fuyong (Yixue xinzhi zazhi)
The 2021 American College of Rheumatology/Vasculitis Foundation guidelines for the management of Kawasaki disease (KD) provided evidence-based recommendations and expert guidance for the treatment of KD, with a focus on clinical situations more commonly handled by rheumatologists. The good practice statement confirmed that all KD patients should receive initial treatment with intravenous immunoglobulin (IVIg). Additionally, the guideline included 7 strong recommendations and 4 conditional recommendations for the treatment of KD or suspected KD.The strong recommendations emphasized the timely treatment of incomplete KD, the use of aspirin therapy, and the performance of echocardiography in cases of macrophage activation syndrome or shock of unknown origin. The conditional recommendations suggested the use of IVIg and other adjunctive therapies for patients with KD who were resistant to IVIg and/or had high-risk features for coronary artery aneurysms. This guideline provided direction on diagnostic strategies, drug selection, and the use of echocardiography for suspected or confirmed KD patients. This article referenced both domestic and international literature to interpret the key points of the guideline, aiming to provide useful insights for pediatricians in China.